In-building wideband multipath characteristics at 2.5 and 60 GHz - Anderson, C.R.; Rappaport, T.S.; Bae, K.; Verstak, A.; Ramakrishnan, N.; Tranter, W.H.; Shaffer, C.A.; Watson, L.T. (Proceedings IEEE 56th Vehicular Technology Conference, 2002)
This paper contains measured data for 2.5 and 60 GHz in-building partition loss. Path loss measurements were recorded using a broadband sliding correlator channel sounder which recorded over 39000 power delay profiles (PDP) in 22 separate locations in a modern office building. Transmitters and receivers were separated by distances ranging from 3.5 to 27.4 meters, and were separated by a variety of obstructions, in order to emulate future single-cell-per-room wireless networks. These measurements may aid in the development of future in-building wireless networks in the unlicensed 2.4 GHz and 60 GHz bands.